Analisis Keaktifan Peserta Didik dalam Penerapan Pembelajaran Matematika Pada Kelas 2 SD dengan Pendekatan TARL - Rahmawati, Ridha; Sulianto, Joko; Nursyarifah, Nining; Prayito, Muhammad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine learning using the TaRL approach on students' activeness in learning mathematics in class II elementary school. This research was conducted in class II B at SD Negeri Palebon 02. This research is a type of qualitative research. Data obtained in this research was obtained by observing the class or observing during the learning process. The type of research data is qualitative data based on learning with the TaRL approach in mathematics subjects regarding fractions. The data sources in this research were class II B students. The data collection techniques used were interviews, observation and documentation. The results of this research showed that students' activeness in learning with the TaRL approach to mathematics learning obtained a good percentage of 84.6%. Learning with the TaRL approach uses steps to group students according to their level of ability, group discussions and presentations in groups that are actively involved and enthusiastic in participating in learning.